An organisation theory perspective of performance measurement systems in public sector organisations - Micheli, Pietro (Cranfield University, 2004)
This dissertation presents a systematic review of the literature (SLR) about the use of two organization theories (OT) - new institutional and resource dependence - in the study of performance measurement (PM) in public sector organizations. The SLR confirmed the findings of a scoping study, namely that two categories of papers exist in this field - theoretical and applied. The majority of papers are applied: they address primarily the practical aspects of PM, but often lack a strong theoretical grounding. Theoretical contributions, on the other hand, rarely deal with practical aspects and the authors seem unconcerned about the relevance of their studies to practitioners. Nevertheless, it is believed that, by creating new knowledge that is firmly grounded in theory and at the same time relevant to practice, it is possible to bridge the gap between the two bodies of literature and further the knowledge of this field. Furthermore, this dissertation shows that the subject of PM could strongly benefit from the use of the two suggested theories, which, despite their dissimilarities, could be conjointly used. The systematic character of the review means that transparency and traceability to the researcher’s decisions and criteria is maintained. The SLR proved to be very relevant in relation to the researcher’s wider subject of interest - the examination of the interactions between institutions and public sector organizations belonging to the same organisational field in the development of PM systems. In this sense, very significant themes emerged from the material included in the SLR. These include the types of strategic responses to institutional pressures and the importance of various concepts drawn from the two bodies of literature, e.g. efficiency, effectiveness, legitimacy, isomorphism, loose coupling, institutionalization and power. Finally, interesting reflections were identified regarding research methods, methodologies and levels of analysis.